Machine-made sand dry hard concrete for airport pavement and preparation method thereof

By improving the quality of the machined sand and reasonably matching the aggregate particles, and using appropriate admixtures, a dry hard machined sand concrete that meets the performance requirements of the airport road surface was prepared, which solved the problem of machined sand performance defects and achieved high bending tensile strength, wear resistance and good construction performance.

CN117383876BActive Publication Date: 2025-04-25CHINA CONSTR WEST CONSTR SOUTHWEST CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311593855.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-27
Publication Date
2025-04-25
Estimated Expiration
2043-11-27

AI Technical Summary

Technical Problem

In areas without natural sand resources, how to prepare a dry hard machine sand concrete that meets the performance requirements of airport road surfaces to solve the problem of defects in machine sand performance.

Method used

By improving the quality of the machine sand, reasonably matching the aggregate particles, and using appropriate admixtures, a dry hard concrete for airport road surface machine sand containing cement, gravel, machine sand, metal slag powder and admixtures are prepared.

Benefits of technology

The application of machined sand in dry hard concrete in airport road surfaces has been realized, and the tensile strength of bending, wear resistance, wool smoothness, construction performance, water retention capacity and reduced shrinkage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117383876B_ABST
    Figure CN117383876B_ABST
Patent Text Reader

Abstract

The invention discloses an airport pavement machine-made sand dry hard concrete, which is characterized by comprising 320-360 kg / m 3 , crushed stone 1350~1450kg / m 3 , machine-made sand 550~600kg / m 3 , metal slag powder 20~40kg / m 3 , admixture 1~2kg / m 3 , water 135~155kg / m 3 ; The admixture composition includes water reducing agent 0.8~1.5kg / m 3 , air entraining agent 0.005~0.01kg / m 3 、Organic phosphonic acid 0.05~0.10kg / m 3 , polyacrylamide 0.03~0.1kg / m 3 , humate 0.1~0.3kg / m 3 The present invention overcomes the performance defects of machine-made sand by improving the quality of machine-made sand, reasonably matching aggregate particles and suitable admixtures, thereby realizing the application of machine-made sand in dry hard concrete of airport pavements, and solving the technical difficulties in constructing airport pavements in vast areas without natural sand resources. The obtained product has the characteristics of high flexural tensile strength, good wear resistance, smooth roughening, good construction performance, strong water retention capacity, and small shrinkage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and particularly relates to an airport pavement machine-made sand dry hard concrete and a preparation method thereof. Background Art

[0002] The main stress characteristic of airport runway concrete is that it repeatedly bears the load caused by the acceleration or deceleration of aircraft of various tonnages, especially for the concrete slabs in the aircraft take-off and landing area, which repeatedly bear huge impact loads. Therefore, airport pavement concrete is different from ordinary concrete for building construction. Airport pavement concrete has strict requirements on raw materials. The existing concrete used for airport pavements is usually prepared with natural sand. However, with the increasing depletion of natural sand and its uneven distribution in various regions, it is extremely difficult to obtain natural sand when building airport pavements in a considerable part of the region. At this time, machine-made sand has obvious economic advantages over natural sand. Compared with natural sand, machine-made sand has a higher stone powder content, rough particle surface, and strong angularity. After using machine-made sand, the newly mixed machine-made sand pavement concrete has a series of disadvantages such as poor workability, large water absorption, difficulty in slurry extraction, too fast consistency loss and difficulty in construction, and poor roughening continuity.

[0003] For the vast areas without natural sand resources, how to prepare a dry and hard machine-made sand concrete that meets the performance requirements of airport pavement has become an urgent problem to be solved. Summary of the invention

[0004] The purpose of the present invention is to provide an airport pavement machine-made sand dry-hard concrete and a preparation method thereof. The performance defects of machine-made sand are overcome by improving the quality of machine-made sand, reasonably matching aggregate particles and suitable admixtures, and the application of machine-made sand in airport pavement-type dry-hard concrete is realized, which solves the technical problem of building airport pavements in vast areas without natural sand resources. The obtained product has the characteristics of high flexural tensile strength, good wear resistance, smooth roughening, good construction performance, strong water retention capacity, small shrinkage, etc.

[0005] In order to achieve the above purpose, the technical solutions adopted are as follows:

[0006] A machine-made sand dry hard concrete for airport pavement, composed of 320-360 kg / m cement 3 , crushed stone 1350~1450kg / m 3 , machine-made sand 550~600kg / m 3 , metal slag powder 20~40kg / m 3 , admixture 1~2kg / m 3 , water 135~155kg / m 3 ;

[0007] The admixture composition includes water reducing agent 0.8~1.5kg / m 3, air entraining agent 0.005~0.01kg / m 3 、Organic phosphonic acid 0.05~0.10kg / m 3 , polyacrylamide 0.03~0.1kg / m 3 , humate 0.1~0.3kg / m 3 .

[0008] According to the above scheme, the cement is silicate cement or ordinary silicate cement, the strength grade is not less than 42.5, the initial setting time is not less than 120 minutes, and the other properties meet the requirements of "General Portland Cement" GB 175-2007.

[0009] According to the above scheme, the metal slag powder is one or more of steel slag powder, lithium slag powder, manganese slag powder, aluminum slag powder and copper slag powder, and its specific surface area is not less than 400m 2 / kg, moisture content not more than 2.0wt%, 28d activity index not less than 95%, loss on ignition not more than 8%.

[0010] According to the above scheme, the crushed stone is 5mm~37.5mm continuously graded crushed stone, among which the mass content of 26.5mm~37.5mm particles is 15%~25%, the mass content of 16.0mm~26.5mm particles is 35%~45%, the tightly packed void ratio is not more than 40%, and the other properties meet the requirements of "Crushed Stone and Pebbles for Construction" GB / T 14685-2022.

[0011] According to the above scheme, the parent rock of the artificial sand is limestone, dolomite, granite or quartzite, the crushing value index is not more than 20%, it belongs to zone II medium sand, the fineness modulus is 2.6-2.8, the mass content of particles below 0.15mm is not more than 5%, the particles above 4.75mm are not more than 1%, the content of particles in the 2.36mm-4.75mm segment is not more than 15%, the angular coefficient is 20%-25%, the water absorption rate is not more than 1.5%, and the other properties meet the requirements of "Construction Sand" GB / T 14684-2022.

[0012] According to the above scheme, the water reducer is a polycarboxylic acid high-performance water reducer with a solid content of 40% to 50%, a water reduction rate of 15% to 20%, and a density of 1.05 to 1.15 g / cm 3 , pH value is 6-8; other properties meet the requirements of "Concrete Admixtures" GB8076-2008.

[0013] According to the above scheme, the air entraining agent is one of rosin air entraining agent and alkylbenzene sulfonate air entraining agent or a mixture of the two, and the effective solid content is not less than 98%; the other properties meet the requirements of "Concrete Admixtures" GB 8076-2008.

[0014] According to the above scheme, the organic phosphonic acid is one or a mixture of phosphonohydroxyacetic acid, hydroxyphenylphosphinopropionic acid, aminotri(methylenephosphonic acid), hydroxyethylidene diphosphonic acid, and phosphoric acid amide, and the effective solid content is 60% to 80%.

[0015] According to the above scheme, the polyacrylamide is a white powder with a molecular weight of 50,000 to 100,000 and a density of 1.25 to 1.35 g / cm 3 .

[0016] According to the above scheme, the fulvic acid salt is one of sodium fulvic acid and potassium fulvic acid or a mixture thereof, the pH value is 6-7, and the soluble fulvic acid content is not less than 70wt%; the biochemical fulvic acid in the effective ingredient is not less than 60wt%, the K2O or Na2O content is not less than 15wt%, and the moisture content is not more than 12wt%.

[0017] The method for preparing the airport pavement machine-made sand dry hard concrete comprises the following steps:

[0018] (1) mixing a water reducing agent, an air entraining agent, an organic phosphonic acid, polyacrylamide, a humate and a portion of the mixing water to obtain an admixture mixture;

[0019] (2) Putting crushed stone, cement, machine-made sand, the admixture mixture and the remaining mixing water into a mixer in sequence and stirring for 2 minutes to 3 minutes to obtain the airport pavement machine-made sand dry hard concrete.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] First of all, the appropriate aggregate gradation has a lower specific surface area and a larger mortar coating thickness, and can ensure that the airport pavement concrete has a more reasonable clamp-lock skeleton structure, which is the basis for ensuring that the airport pavement concrete has better mechanical properties and durability. Therefore, the present invention sets the gradation range and compact packing density of coarse aggregate and machine-made sand. In addition, the range of the angular coefficient of machine-made sand is set to ensure that the machine-made sand has a good grain shape and can be well matched.

[0022] On the one hand, metal slag powder has high activity and can act as an admixture in concrete. It can fill the pores in machine concrete, improve the density of dry hard concrete of airport pavement, and improve the workability, mechanical properties and wear resistance of dry hard concrete. On the other hand, metal ions can be ionized in metal slag powder, which can react with fulvic acid salt at an early stage, weaken the electrostatic adsorption between polyacrylamide, and inhibit the flocculation of polyacrylamide. In addition, the competition and vacancy crowding between the metal ions ionized by metal slag powder can promote the reaction between tetracalcium aluminoferrate in cement and calcium ions and silicate ions in cement stone to generate silicate hydrates and calcium aluminoferrate and other compounds, thereby improving the flexural strength and stability of cement.

[0023] The water reducing agent in the admixture can reduce the water consumption and improve the workability of concrete. The air entraining agent in the admixture can introduce a certain amount of bubbles, play a ball effect, improve the workability of concrete, and reduce the water bleeding rate of dry hard concrete, reducing the sensitivity to water consumption and water reducing agent dosage.

[0024] The organic phosphonic acid in the admixture has good adaptability to polycarboxylate water reducer and cement, and has good adaptability to Ca 2+ Mg 2+ , Fe 2 + 、Zn 2+ It has a strong chelating effect on metal ions and can effectively reduce the hydration heat release rate and heat release of cement within a certain dosage range, improve the hydration heat release process of silicate cement, have a good retarding effect, extend the construction operability of dry-hard concrete, and facilitate the premixed transportation of machine-made sand dry-hard concrete.

[0025] The polyacrylamide in the admixture mainly plays multiple roles such as water retention, thickening, bonding, lubrication, and flocculation. In particular, the water retention and lubrication effects can improve the interaction between particles in the fresh concrete, making it difficult for the concrete water to be lost, increasing the mechanical properties of the concrete, and improving the toughness of the concrete. It can not only improve the flexural tensile strength of the concrete, but also improve its flexural toughness and abrasion resistance. In addition, it can also reduce the compression ratio, permeability, and shrinkage. However, polyacrylamide has a strong flocculation effect, which can reduce the fluidity of the slurry and is not conducive to the workability of the concrete. The high-valent metal ions ionized by humic acid salt and metal slag powder can be electrically neutralized with anionic polyacrylamide in the early stage, weakening the electrostatic adsorption between polyacrylamide, so that the water retention effect of polyacrylamide is enhanced, while the flocculation effect is inhibited, thereby improving the workability of the airport pavement machine-made sand dry hard concrete. In the later stage, as the high-valent metal ions ionized from the metal slag powder are gradually solidified, the flocculation effect of polyacrylamide is reactivated, which is beneficial to the stability of the airport pavement machine-made sand dry hard concrete after construction and paving, reduces the occurrence of the "spring material" phenomenon, and is also beneficial to the smoothing and roughening construction.

[0026] The molecular weight of the humate in the admixture is relatively small. It has anti-flocculation and buffering effects in the early stage of hydration of fresh concrete, good solubility, strong interaction with metal ions, and can have complexation with dissolved metal ions such as metal slag, and can be electrically neutralized with anionic polyacrylamide, effectively weakening the electrostatic adsorption between polyacrylamide, inhibiting the flocculation of polyacrylamide, and improving the working performance of the machine-made sand dry hard concrete of the airport pavement. At the same time, humate is a colloidal organic substance that can form a colloid in the concrete, cementing the small particles in the concrete, and has strong water retention. It can also improve the smoothness and continuity of the airport pavement concrete during the roughening process, and keep the texture after roughening from collapsing, and improve the return of water on the surface of the machine-made sand dry hard concrete.

[0027] The airport pavement machine-made sand concrete prepared by the present invention has good slurry encapsulation, uniformity and water retention, and can realize a long-term controllable operation time of the airport pavement machine-made sand concrete construction, meet the requirements of pre-mixed long-distance transportation, and the surface roughening is smooth and has strong continuity and low water bleeding rate; at the same time, the hardened airport pavement concrete has high flexural tensile strength, excellent wear resistance and low shrinkage, and is suitable for promotion and application in areas with scarce natural sand resources. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 : Early autogenous shrinkage deformation rate of concrete obtained in Examples 1-9. DETAILED DESCRIPTION

[0029] The following examples further illustrate the technical solution of the present invention, but are not intended to limit the scope of protection of the present invention.

[0030] The specific implementation method provides an airport pavement machine-made sand dry hard concrete, which is composed of cement 320-360 kg / m 3 , crushed stone 1350~1450kg / m 3 , machine-made sand 550~600kg / m 3 , metal slag powder 20~40kg / m 3 , admixture 1~2kg / m 3 , water 135~155kg / m 3 ;

[0031] The admixture composition includes water reducing agent 0.8~1.5kg / m 3 , air entraining agent 0.005~0.01kg / m 3 、Organic phosphonic acid 0.05~0.10kg / m 3 , polyacrylamide 0.03~0.1kg / m 3 , humate 0.1~0.3kg / m 3 .

[0032] Specifically, the cement is silicate cement or ordinary silicate cement, with a strength grade of not less than 42.5, an initial setting time of not less than 120 minutes, and other properties comply with the requirements of "General Purpose Portland Cement" GB 175-2007.

[0033] Specifically, the metal slag powder is one or more of steel slag powder, lithium slag powder, manganese slag powder, aluminum slag powder, and copper slag powder, and its specific surface area is not less than 400m 2 / kg, moisture content not more than 2.0wt%, 28d activity index not less than 95%, loss on ignition not more than 8%.

[0034] Specifically, the crushed stone is a continuously graded crushed stone of 5mm to 37.5mm, wherein the mass content of 26.5mm to 37.5mm particles is 15% to 25%, the mass content of 16.0mm to 26.5mm particles is 35% to 45%, the tightly packed void ratio is not more than 40%, and the other properties meet the requirements of "Crushed Stone and Pebbles for Construction" GB / T 14685-2022.

[0035] Specifically, the parent rock of the artificial sand is limestone, dolomite, granite or quartzite, the crushing value index is not more than 20%, it belongs to zone II medium sand, the fineness modulus is 2.6-2.8, the mass content of particles below 0.15 mm is not more than 5%, the particles above 4.75 mm are not more than 1%, the content of particles in the 2.36 mm-4.75 mm segment is not more than 15%, the angular coefficient is 20%-25%, the water absorption rate is not more than 1.5%, and the other properties meet the requirements of "Construction Sand" GB / T 14684-2022.

[0036] Specifically, the water reducer is a polycarboxylic acid high-performance water reducer with a solid content of 40% to 50%, a water reduction rate of 15% to 20%, and a density of 1.05 to 1.15 g / cm 3 , pH value is 6-8; other properties meet the requirements of "Concrete Admixtures" GB 8076-2008.

[0037] Specifically, the air entraining agent is one of rosin-based air entraining agents and alkylbenzene sulfonate-based air entraining agents or a mixture of the two, and the effective solid content is not less than 98%; the other properties meet the requirements of "Concrete Admixtures" GB 8076-2008.

[0038] Specifically, the organic phosphonic acid is one or a mixture of phosphonohydroxyacetic acid, hydroxyphenylphosphoropropionic acid, aminotri(methylenephosphonic acid), hydroxyethylidene diphosphonic acid, and phosphoric acid amide, and the effective solid content is 60% to 80%.

[0039] Specifically, the polyacrylamide is a white powder with a molecular weight of 50,000 to 100,000 and a density of 1.25 to 1.35 g / cm 3 .

[0040] Specifically, the fulvic acid salt is one of sodium fulvic acid and potassium fulvic acid or a mixture thereof, with a pH value of 6-7 and a soluble fulvic acid content of not less than 70wt%; the biochemical fulvic acid in the effective ingredients is not less than 60wt%, the K2O or Na2O content is not less than 15wt%, and the moisture content is not more than 12wt%.

[0041] The specific implementation also provides a method for preparing the above-mentioned airport pavement machine-made sand dry hard concrete, comprising the following steps:

[0042] (1) mixing a water reducing agent, an air entraining agent, an organic phosphonic acid, polyacrylamide, a humate and a portion of the mixing water to obtain an admixture mixture;

[0043] (2) Putting crushed stone, cement, machine-made sand, the admixture mixture and the remaining mixing water into a mixer in sequence and stirring for 2 minutes to 3 minutes to obtain the airport pavement machine-made sand dry hard concrete.

[0044] The technical solution of the present invention is compared with ordinary machine-made sand dry-hard concrete. The total amount of cementitious materials in concrete of each strength grade remains unchanged, and the amount of fine aggregate, crushed stone, admixture and water in concrete of each strength grade is kept fixed. The benchmark mix ratio (blank group) is shown in Table 1. The raw materials in Table 1 are of conventional types, among which the fly ash is Class I fly ash, and its technical performance meets the relevant provisions of "Fly Ash Used in Cement and Concrete" GB / T 1596-2017; the crushed stone adopts conventional 5.0mm~31.5mm continuous graded crushed stone, among which the mass content of 26.5.0mm~31.5mm particles is 15%, the mass content of 16.0mm~26.5mm particles is 50%, the mass content of 9.5mm~16.0mm particles is 10%, the mass content of 5.0mm~9.5mm particles is 25%, the close-packed void ratio is 42%, and the other properties meet the requirements of "Crushed Stone and Pebbles for Construction" GB / T14685-2022; the machine-made sand is made of conventional limestone or pebbles Machine-made sand, medium sand in zone II, fineness modulus of 2.8, mass content of particles above 4.75 mm is 3%, mass content of particles from 2.36 mm to 4.75 mm is 20%, mass content of particles from 1.18 mm to 2.36 mm is 20%, mass content of particles from 0.60 mm to 1.18 mm is 15%, mass content of particles from 0.30 mm to 0.60 mm is 18%, mass content of particles from 0.15 mm to 0.30 mm is 16%, mass content of particles below 0.15 mm is 8%, angular coefficient is 28%, and other properties meet the requirements of "Construction Sand" GB / T 14684-2022; the common admixture used in Example 1 is a water reducer, wherein the admixture composition includes 0.7 kg / m 3 , slump retaining agent 0.172kg / m 3 , air entraining agent 0.08kg / m 3 , white sugar 0.06kg / m 3 , sodium gluconate 0.06kg / m 3 The common admixture of Example 2 is a water reducer, wherein the admixture composition includes a water reducer 1.0 kg / m 3 , collapse-preventing agent 0.232kg / m 3 , air entraining agent 0.008kg / m 3 , white sugar 0.08kg / m 3 , sodium gluconate 0.08kg / m 3 The common admixture of Example 3 is a water reducer, wherein the admixture composition includes 1.3 kg / m 3 , collapse-preventing agent 0.29kg / m 3 , air entraining agent 0.01kg / m 3 , white sugar 0.1kg / m 3 , sodium gluconate 0.1kg / m 3.

[0045] The specific ingredients and dosages of the embodiments of the present invention are shown in Table 2.

[0046] Table 1: Mix ratio information of dry hard concrete of Example 1-3 (kg / m 3 )

[0047] Serial number Strength level cement Fly ash gravel Machine-made sand Water consumption Common admixtures 1 C40 320 20 1420 580 150 1.0 2 C50 340 20 1400 580 145 1.4 3 C60 360 30 1380 560 140 1.8

[0048] Table 2: Mix ratio information of dry hard concrete of Example 4-9 (kg / m 3 )

[0049]

[0050] The above experimental examples 1-9 were tested and verified using a vertical axis planetary mixer with a maximum single mixing volume of 3m 2 The trial matching steps are:

[0051] (1) Accurately weigh 2m 2 Test the required materials, control the error of aggregate to be less than ±1.0%, the error of powder to be less than ±0.5%, and the error of liquid to be less than ±0.2%;

[0052] (2) Stir the weighed water reducer, air entraining agent, organic phosphonic acid, polyacrylamide, humic acid salt and part of the mixing water for 5 to 8 minutes to form a mixed solution;

[0053] (3) The crushed stone, cement, machine-made sand, mixed liquid and the remaining mixing water are sequentially put into a mixer and stirred for 2 to 3 minutes to obtain the airport pavement machine-made sand dry hard concrete.

[0054] (4) After leaving the machine, use Vebe consistency to test the workability of dry hard concrete mixture. After 3 hours, use Vebe consistency to test the workability of concrete again. Generally speaking, the smaller the Vebe consistency (time value), the better the workability of concrete. Refer to the "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete" GBT50082-2009 to test the change in self-shrinkage of concrete from the time it leaves the pot to the third day, and use a contact stand to test the change in drying shrinkage of concrete.

[0055] (5) One hour after the concrete leaves the machine, a rectangular block of 2m×2m×0.4m is formed to simulate the airport pavement. According to the airport road concrete construction process, an inserted vibrating rod is used to vibrate and compact the concrete, and the surface is smoothed by slurry. Two hours after the concrete is formed, a roughening test is carried out to test the roughening depth and continuity, and the amount of water returned from the concrete surface is also tested.

[0056] (6) The test method for concrete wear resistance is carried out in accordance with JTG E30-2005 “Test Procedure for Cement and Cement Concrete for Highway Engineering”; the test specimen is a standard concrete specimen (150 mm × 150 mm × 150 mm).

[0057] The basic properties of concrete in each experimental example are shown in Table 3. Figure 1 As shown in the figure, a positive deformation rate indicates that the concrete specimen has become longer, and a negative deformation rate indicates that the concrete specimen has become shorter.

[0058] Table 3 Basic properties of test mix concrete of test groups 1-18

[0059]

[0060] It can be seen from Table 3 above that with the increase of strength grade, the workability, roughening depth and mechanical properties of concrete show an overall trend of improvement, while the wear value and drying shrinkage rate show an overall downward trend. It can be seen from Examples 1 / 4 / 5, 2 / 6 / 7, 3 / 8 / 9 respectively that under the same strength grade, the Vebe consistency value of the airport road machine-made sand dry hard concrete using the present invention is relatively low, and the increase value and amplitude of the Vebe consistency value after 3 hours are significantly lower. At the same time, the 3h roughening depth under the same strength grade is deeper, and the coherence of the roughening is stronger, which shows that the present invention has better workability and longer construction operability. It can also be seen from Examples 1 / 4 / 5, 2 / 6 / 7, 3 / 8 / 9 that the return water volume of the present invention is significantly lower, indicating that the present invention helps to control the seepage after the airport pavement construction, reduce the quality risk caused by the seepage, and lay a foundation for improving the surface performance of the airport pavement machine-made sand dry hard concrete. It can also be seen from Examples 1 / 4 / 5, 2 / 6 / 7, 3 / 8 / 9 that under the same strength grade, the flexural tensile strength and compressive strength of the embodiments of the present invention are higher than those of the comparative examples, indicating that the present invention can activate the hydration performance of the cementitious material in the concrete and improve the strength of the concrete. At the same time, the flexural-compression ratio of the embodiments of the present invention is also higher than that of the comparative examples, indicating that the airport road machine-made sand dry-hard concrete of the present invention has good toughness. In addition, it can be seen from Table 3 that with the increase of strength grade and the increase of cementitious material in the concrete, the wear resistance of the concrete is improved as a whole, while the drying shrinkage rate shows an overall downward trend; at the same time, the airport road machine-made sand dry-hard concrete of the present invention with the same strength grade has lower wear resistance and drying shrinkage values, that is, the effects of various substances such as polyacrylamide and metal slag powder in the present invention, on the one hand, improve the compactness of the concrete, and on the other hand, the complexation or chelation between multiple ions under the mediation of humic acid salts activates the potential activity, thereby improving the surface wear resistance and reducing the shrinkage value of the concrete. Figure 1It can be seen that with the increase of strength grade, the increase of cementitious materials, and the increase of hydration reaction substances, the early self-shrinkage of concrete shows an overall increasing trend. At the same time, the early self-shrinkage value of the embodiment of the present invention in the barrel strength grade is significantly smaller than that of the respective comparative examples, and the time for the self-shrinkage to reach a substantially unchanged state is prolonged, indicating that the effective ingredients in the present invention can improve the hydration reaction of concrete, appropriately delay the setting time of concrete, and slowly release the hydration heat, which is helpful to reduce the early self-shrinkage of concrete and reduce the risk of cracking, and is of great significance to the volume stability of airport pavement.

[0061] In summary, the embodiments of the present invention have no adverse effect on the working performance of concrete, can improve water retention, reduce workability loss, improve and compensate for the autogenous shrinkage and drying shrinkage performance of concrete, weaken the adverse effect of further expansion and cracking of concrete caused by the later production of dihydrate gypsum by solid sulfur ash, and the scope of application is expanded, with good economic and social benefits.

Claims

1. An airport pavement machine-made sand dry hard concrete, characterized in that Composition: cement 320~360kg / m 3 , crushed stone 1350~1450kg / m 3 , machine-made sand 550~600kg / m 3 , metal slag powder 20~40kg / m 3 , admixture 1~2kg / m 3 , water 135~155kg / m 3 ; The admixture composition includes water reducing agent 0.8~1.5kg / m 3 , air entraining agent 0.005~0.01kg / m 3 、Organic phosphonic acid 0.05~0.10kg / m 3 , polyacrylamide 0.03~0.1kg / m 3 , humate 0.1~0.3kg / m 3 .

2. The airport pavement machine-made sand dry hard concrete as claimed in claim 1, characterized in that The cement is silicate cement or ordinary silicate cement, with a strength grade of not less than 42.5, an initial setting time of not less than 120 minutes, and other properties comply with the requirements of "General Purpose Portland Cement" GB 175-2007.

3. The airport pavement machine-made sand dry hard concrete as claimed in claim 1, characterized in that The metal slag powder is one or more of steel slag powder, lithium slag powder, manganese slag powder, aluminum slag powder and copper slag powder, and its specific surface area is not less than 400m 2 / kg, moisture content not more than 2.0wt%, 28d activity index not less than 95%, loss on ignition not more than 8%.

4. The airport pavement machine-made sand dry hard concrete as claimed in claim 1, characterized in that The crushed stone is a continuously graded crushed stone of 5mm~37.5mm, of which the mass content of 26.5mm~37.5mm particles is 15%~25%, the mass content of 16.0mm~26.5mm particles is 35%~45%, the tightly packed void ratio is not more than 40%, and the other properties comply with the requirements of "Crushed Stone and Pebbles for Construction" GB / T14685-2022.

5. The airport pavement machine-made sand dry hard concrete as claimed in claim 1, characterized in that The parent rock of the artificial sand is limestone, dolomite, granite or quartzite. The crushing value index is not more than 20%, which belongs to Zone II medium sand. The fineness modulus is 2.6~2.8, the mass content of particles below 0.15mm is not more than 5%, the particles above 4.75mm are not more than 1%, the content of particles in the 2.36mm-4.75mm segment is not more than 15%, the angular coefficient is 20%~25%, the water absorption rate is not more than 1.5%, and the other properties meet the requirements of "Construction Sand" GB / T14684-2022.

6. The airport pavement machine-made sand dry hard concrete as claimed in claim 1, characterized in that The water reducer is a polycarboxylic acid high-performance water reducer with a solid content of 40% to 50%, a water reduction rate of 15% to 20%, and a density of 1.05 to 1.15 g / cm 3 , pH value is 6-8; the air-entraining agent is one of rosin-based air-entraining agent and alkylbenzene sulfonate-based air-entraining agent or a mixture of the two, and the effective solid content is not less than 98%; the other properties of the water-reducing agent and the air-entraining agent meet the requirements of "Concrete Admixtures" GB 8076-2008.

7. The airport pavement machine-made sand dry hard concrete as claimed in claim 1, characterized in that The organic phosphonic acid is one or a mixture of phosphonohydroxyacetic acid, aminotri(methylenephosphonic acid) and hydroxyethylidene diphosphonic acid, and has an effective solid content of 60% to 80%.

8. The airport pavement machine-made sand dry hard concrete as claimed in claim 1, characterized in that The polyacrylamide is a white powder with a molecular weight of 50,000-100,000 and a density of 1.25-1.35 g / cm 3 .

9. The airport pavement machine-made sand dry hard concrete as claimed in claim 1, characterized in that The fulvic acid salt is one of sodium fulvic acid and potassium fulvic acid or a mixture thereof, with a pH value of 6-7 and a soluble fulvic acid content of not less than 70wt%; the biochemical fulvic acid in the effective ingredients is not less than 60wt%, the K2O or Na2O content is not less than 15wt%, and the moisture content is not more than 12wt%.

10. The method for preparing the airport pavement machine-made sand dry hard concrete according to any one of claims 1 to 9, characterized in that The following steps are involved: (1) Mixing the water reducing agent, air entraining agent, organic phosphonic acid, polyacrylamide, humic acid salt and part of the mixing water to obtain an admixture mixture; (2) Putting crushed stone, cement, machine-made sand, the admixture mixture and the remaining mixing water into a mixer in sequence and stirring for 2 min to 3 min to obtain the airport pavement machine-made sand dry hard concrete.

Citation Information

Patent Citations

  • Impermeable anti-cracking concrete

    CN104072041A

  • Crack-resistant sulphate aluminum cement plant fiber product and preparation method thereof

    CN105645889A